FOOTNOTES. - Myers, John H. (The Accounting Review, 1959)
Abstract Thirty years ago footnotes in annual reports to stockholders were rare; today, published statements seldom are without them. Not only are footnotes frequent and numerous, but also they maybe very important in the interpretation of the statements. Footnotes must be read, not because all footnotes are important, but because one may be vital. Some seem to me to contradict what is said on the face of the statements. Others replace that which is ordinarily on the statements. The purpose of this article is to present the results of my analysis of the notes in the statements of one hundred sixty different companies and to offer some suggestions for improving our presentation of financial statement information. Many of the footnotes to financial statements seem to contradict what is said on the face of the statements. Generally accepted accounting principles require disclosure of the facts, yet today's common conventions do not get all the facts onto the statements. These problems are discussed in detail in the article.